A Persistently High End-Tidal Carbon Dioxide Value: Can This Be Spurious? - Bindu, Barkha; Singh, Gyaninder P.; Jain, Varun; Chaturvedi, Arvind (Journal of Neuroanaesthesiology and Critical Care, 2019)
End-tidal carbon dioxide (EtCO2) monitoring has now become the standard of care not only during anesthesia but also in intensive care units for patients on mechanical ventilation, emergency department, and pre-hospital settings to confirm and monitor the correct placement of endotracheal tube. It is a non-invasive and continuous method of measuring exhaled carbon dioxide (CO2). Continuous waveform capnography measures EtCO2 and monitors ventilation. EtCO2 often correlates with partial pressure of carbon dioxide in arterial blood (PaCO2) and is a reliable indicator of PaCO2. A rise in EtCO2 often implies increased production of CO2 or decreased excretion (rebreathing, decrease ventilation) of CO2. We report an unusual case where the monitor malfunction per se lead to spuriously increased EtCO2 values without any clinical cause and did not correlate with PaCO2, thereby re-emphasizing that various monitors must always be interpreted in correlation with clinical observation.
Keywords: end-tidal carbon dioxide; monitor malfunction; anesthesia; capnography